LEGAL AND SOCIAL RIGHTS TO LGBTQIA+COMMUNITY IN INDIA - Choudhary, Sneha; Kumar, Sarvesh (ShodhKosh: Journal of Visual and Performing Arts, 2022)
LGBTQ+ rights in India have seen significant progress in recent years, yet LGBTQ+ individuals still encounter various social and legal challenges compared to their non-LGBTQ+ counterparts. The judiciary, government, and public each have roles to play: the courts must issue fair and just rulings, the government must ensure these rulings are communicated effectively, and the public must embrace these decisions. Despite the landmark 2018 Supreme Court ruling in Navtej Singh Johar vs. Union of India, which decriminalized homosexuality by striking down parts of Section 377 of the Indian Penal Code, the government and society have not fully capitalized on this progress. Nearly 30 months after the ruling, the situation for the LGBTQ+ community has not significantly improved. Both central and state governments have failed to implement special provisions for the upliftment of LGBTQ+ individuals, and societal acceptance remains limited. This paper examines the prolonged struggle of the LGBTQ+ community for fundamental rights and the discrimination they face, with a particular focus on transgender individuals and judicial pronouncements. It also explores the necessary legal and social changes required for LGBTQ+ individuals to achieve full acceptance and equality in India's conservative society.